2021
DOI: 10.3389/fimmu.2021.665522
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Complete and Fast Recovery From Severe COVID-19 in a Pemphigus Patient Treated With Rituximab

Abstract: COVID-19 is characterized by a severe pulmonary disease due to severe acute respiratory syndrome (SARS)-CoV-2 infection. For clinicians involved in the management of patients with chronic autoimmune diseases the risk linked to the conditions itself and to drug-induced immunosuppression during the COVID-19 pandemic is a major topic. Pemphigus is a rare autoimmune blistering disease (AIBD) of the skin and mucous membranes caused by autoantibodies to desmosomal components, desmoglein 1 and 3. Among immunosuppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…The data of a pemphigus foliaceus patient who was infected by SARS‐CoV‐2 2 months after RTX infusion were reported. She required hospitalization but did not need intensive care, and she completely recovered 2 . An article from Italy reported that 19.4% of AIBDs patients experienced mild to moderate symptoms, while one PV patient (3.2%) with previous breast cancer required hospitalization but later recovered 14 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The data of a pemphigus foliaceus patient who was infected by SARS‐CoV‐2 2 months after RTX infusion were reported. She required hospitalization but did not need intensive care, and she completely recovered 2 . An article from Italy reported that 19.4% of AIBDs patients experienced mild to moderate symptoms, while one PV patient (3.2%) with previous breast cancer required hospitalization but later recovered 14 .…”
Section: Discussionmentioning
confidence: 98%
“…She required hospitalization but did not need intensive care, and she completely recovered. 2 An article from Italy reported that 19.4% of AIBDs patients experienced mild to moderate symptoms, while one PV patient (3.2%) with previous breast cancer required hospitalization but later recovered. 14 Shahidi‐Dadras et al reported five COVID‐19 cases with a mild or moderate course in the total 45 RTX treated pemphigus patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 89 ] A case report also documents the uncomplicated recovery of a COVID-19-infected patient with pemphigus vulgaris who had received a top-up dose of rituximab to control disease flare shortly before infection. [ 90 ] Because of associated prothrombotic risk, patients suffering from comorbid autoimmune blistering disorders and COVID-19 may benefit from low-dose aspirin to reduce morbidity and mortality rates. [ 91 ] Patients on recurrent rituximab dosing may benefit from immunoglobulin level testing.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the conditions above, the dose of methylprednisolone could not be further increased. It is also difficult to use rituximab which may induce a prolonged B-cell depletion and aggravate infections ( 7 ). To improve therapy, dupilumab (600 mg subcutaneously initially and 300 mg subcutaneously every other week) was added to his regimen combined with methylprednisolone, anti-TB regular regimen, and antibiotics plus low-dose intravenous immunoglobulin (15 g IVIG for 4 d) for anti-infection ( Figure 2A ).…”
Section: Case Presentationmentioning
confidence: 99%